Estereotipos sobre España en el paisaje lingüístico de París - Mercè Pujol Berché; Noemí Rámila Díaz (Amnis)
The aim of this article is the analysis of the linguistic landscape –the presence of the Spanish language in the public space (signage, billboards, posters, neon signs, etc.)– of the city of Paris, with a focus on the degree of fossilization of certain stereotypes or parts of them, in the collective imagination. Our objective is to study from a transnational perspective, the instrumentalisation of Spanish stereotypes in the Parisian linguistic landscape in order to observe how Spanish identity is articulated in France, the receiving country. To do so, we have examined the linguistic landscape of shops and businesses (so called « Spanish » bars, restaurants). This perspective will enable us to analyze in a non-Spanish speaking country, therefore the exo-group, the articulation of national identities and other groups, one of the issues tackled in the present monograph.